Heat shock transcription factor 1-activating compounds suppress polyglutamine-induced neurodegeneration through induction of multiple molecular chaperones. - Fujikake, N.; Nagai, Y.; Popiel, H.A.; Okamoto, Y.; Yamaguchi, M.; Toda, T. (Journal of Biological Chemistry, 2008)
Many neurodegenerative diseases including Alzheimer, Parkinson, and polyglutamine (polyQ) diseases are thought to be caused by protein misfolding. The polyQ diseases, including Huntington disease and spinocerebellar ataxias (SCAs), are caused by abnormal expansions of the polyQ stretch in disease-causing proteins, which trigger misfolding of these proteins, resulting in their deposition as inclusion bodies in affected neurons. Although genetic expression of molecular chaperones has been shown to suppress polyQ protein misfolding and neurodegeneration, toward developing a therapy, it is ideal to induce endogenous molecular chaperones by chemical administration. In this study, we assessed the therapeutic effects of heat shock transcription factor 1 (HSF1)-activating compounds, which induce multiple molecular chaperones, on polyQ-induced neurodegeneration in vivo. We found that oral administration of 17-(allylamino)-17-demethoxygeldanamycin (17-AAG) markedly suppresses compound eye degeneration and inclusion body formation in a Drosophila model of SCA. 17-AAG also dramatically rescued the lethality of the SCA model (74.1% rescue) and suppressed neurodegeneration in a Huntington disease model (46.3% rescue), indicating that 17-AAG is widely effective against various polyQ diseases. 17-AAG induced Hsp70, Hsp40, and Hsp90 expression in a dose-dependent manner, and the expression levels correlated with its therapeutic effects. Furthermore, knockdown of HSF1 abolished the induction of molecular chaperones and the therapeutic effect of 17-AAG, indicating that its therapeutic effects depend on HSF1 activation. Our study indicates that induction of multiple molecular chaperones by 17-AAG treatment is a promising therapeutic approach for a wide range of polyQ diseases and possibly other neurodegenerative diseases.